Blood glucose monitor / Muhammad Solehin Jasni, Muhammad Naim Mazlan and Muhammad Irfan Jamilludin - Jasni, Muhammad Solehin; Mazlan, Muhammad Naim; Jamilludin, Muhammad Irfan (2014)
The Blood Glucose Monitor is a device that act as technology based on healthcare. This device is suitable for all user either the adults or teenagers. This project was simulated by ‘Proteus 8 Professional’ software. The Glucose Monitor incorporates features that accommodate diabetic patients with a variety of disabilities such as impaired vision, complete blindness, and impaired movement. This project was also attached with a LCD to indicate the instruction of the moving. These included features are a legible LCD screen as a result.